2019
DOI: 10.1039/c9tc01009b
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of non-reversible thermally enhanced upconversion luminescence behavior in rare-earth doped nanoparticles

Abstract: Volatilization of surface moieties and sintering of the particles both contribute to thermally activated enhancement of upconversion emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Meanwhile, Qiu's group reported the thermally enhanced UCL in core-only Yb 3+ /Tm 3+ β-NaGdF4 UCNPs. It was found that the particle sintering process proceeded at high temperatures (>500 K) and caused the irreversible thermal enhancement of UCL 56 (Fig. 5c-d).…”
Section: Understanding the Possible Underpinning Mechanisms Explainin...mentioning
confidence: 98%
“…Meanwhile, Qiu's group reported the thermally enhanced UCL in core-only Yb 3+ /Tm 3+ β-NaGdF4 UCNPs. It was found that the particle sintering process proceeded at high temperatures (>500 K) and caused the irreversible thermal enhancement of UCL 56 (Fig. 5c-d).…”
Section: Understanding the Possible Underpinning Mechanisms Explainin...mentioning
confidence: 98%
“…With the deepening of the studies on the up‐conversion of rare earth (RE) doped materials recently, it has shown great potential in the fields of temperature sensing, anti‐counterfeiting technology and biological imaging . The lanthanide RE ions becomes an excellent choice for up‐conversion luminescence, because of their multistage metastable energy level structure.…”
Section: Introductionmentioning
confidence: 99%
“…23 In this regard, it is easy to accept that heating-induced desorption of water molecules from UCNPs’ surfaces can naturally lead to the alleviation of surface quenching. 24,25 The amount of water molecules that can be absorbed (desorbed) to (from) the surfaces of UCNPs is directly associated with, again, the surface-to-volume ratio. Since smaller UCNPs featuring a higher surface-to-volume ratio will absorb more water molecules and suffer more serious surface quenching, more dissipation energy will be recovered by means of the heating-induced desorption of water molecules from smaller UCNPs.…”
Section: Resultsmentioning
confidence: 99%